Assessing the consequences of gestational diabetes mellitus on offspring’s cardiovascular health: MySweetHeart Cohort study protocol, Switzerland - Di Bernardo, Stefano (BMJ Open, 2017)
INTRODUCTION: Gestational diabetes mellitus (GDM) is a state of glucose intolerance with onset during pregnancy. GDM carries prenatal and perinatal risks as well as long-term risks for the mother and her child. GDM may be involved in the foetal programming of long-term cardiovascular health. However, evidence is sparse and the effect of GDM on cardiovascular health is unknown. To address these issues, we will conduct MySweetHeart Cohort study. The objectives are to assess the effect of GDM on offspring’s cardiovascular health early in life by using surrogate markers of cardiovascular disease and atherosclerosis. METHODS AND ANALYSIS: This is a cohort study of 100 offspring of women with GDM and 100 offspring of women without GDM. At inclusion, a baseline assessment of the mothers will be conducted through means of self-report questionnaires, a researcher-administrated interview, blood pressure and anthropometric measurements, and a maternal blood sampling. Between the 30th and 34th weeks of gestation, a foetal echography will be performed to assess the foetal cardiac structure and function, the fetomaternal circulation and the hepatic volume. At birth, maternal and neonatal characteristics will be assessed. An echocardiography will be performed to assess cardiac structure and function 2–7 days after birth; carotid intima-media thickness will be also measured to assess vascular structure. MySweetHeart Cohort is linked to MySweetHeart Trial (clinicaltrials.gov/ct2/show/NCT02890693), a randomised controlled trial assessing the effect of a multidimensional interdisciplinary lifestyle and psychosocial intervention to improve the cardiometabolic and mental health of women with GDM and their offspring. A long-term follow-up of children is planned. ETHICS AND DISSEMINATION: Ethical approval has been obtained through the state Human Research Ethics Committee of the Canton de Vaud (study number 2016–00745). We aim to disseminate the findings through regional, national and international conferences and through peer-reviewed journals. TRIAL REGISTRATION NUMBER: ClinicalTrials.gov (clinicaltrials.gov/ct2/show/NCT02872974).